2021
DOI: 10.1038/s41598-021-93317-2
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin maintenance dose prediction for Chinese after heart valve replacement by a feedforward neural network with equal stratified sampling

Abstract: Patients requiring low-dose warfarin are more likely to suffer bleeding due to overdose. The goal of this work is to improve the feedforward neural network model's precision in predicting the low maintenance dose for Chinese in the aspect of training data construction. We built the model from a resampled dataset created by equal stratified sampling (maintaining the same sample number in three dose-groups with a total of 3639) and performed internal and external validations. Comparing to the model trained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Furthermore, clinical data such as age, sex, and history of the disease are important for clinical treatment (42). There was no significant difference between the efficacy and inefficacy groups in terms of age, sex, hypertension, or MISPT history in our study; this result is similar to that reported in the literature (33).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, clinical data such as age, sex, and history of the disease are important for clinical treatment (42). There was no significant difference between the efficacy and inefficacy groups in terms of age, sex, hypertension, or MISPT history in our study; this result is similar to that reported in the literature (33).…”
Section: Discussionsupporting
confidence: 89%
“…[ 2 ]. The clinical manifestations are valvular insufficiency, stenosis resulting in increased cardiac load, and cardiac insufficiency [ 3 ]. A common treatment method for this disease is heart valve replacement for both middle and advanced level rheumatic heart disease, mainly replacing the diseased valve with an artificial valve to improve clinical symptoms, and the operation is usually carried out under cardiopulmonary bypass [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, ML algorithms could be applied to develop predictive models to optimize warfarin dosing, using either regression or multi classification models. Nine studies were included [96][97][98][99][100][101][102][103][104] . Most of them derive from a multiethnic International Warfarin Pharmacogenetics Consortium (IWPC) dataset 105 using several ML regression models (Supplementary Table 5).…”
Section: Prediction Of a Personalized Anticoagulant Managementmentioning
confidence: 99%
“…Nine studies were included. 96 97 98 99 100 101 102 103 104 Most of them derive from a multiethnic International Warfarin Pharmacogenetics Consortium (IWPC) dataset 105 using several ML regression models ( Supplementary Table S5 , available in the online version). Sharabiani et al 96 have incorporated patient-specific clinical and genetic data to predict a personalized warfarin dose in the IWPC dataset using relevance vector machines.…”
Section: Prediction Of a Personalized Anticoagulant Managementmentioning
confidence: 99%